2021
DOI: 10.3390/psych3040049
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Hospitalizations and Length of Hospital Stay in Patients with Schizophrenia Spectrum Disorders or Bipolar Disorder Treated in a Mobile Mental Health Service in Insular Greece

Abstract: In recent years serious mental health issues, such as schizophrenia spectrum disorders and bipolar disorder, have been treated in the community by community-based mental health services. In the present study our goal was to estimate the modification in the number of hospitalizations and duration of admissions in either psychotic patients or patients with bipolar disorder, treated by a Mobile Mental Health Unit in the islands of Kefalonia, Zakynthos and Ithaca (MMHU-KZI). Data were collected from a total of 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The number of hospitalizations did not differ statistically between the two groups of patients. It has been previously shown that treatment delivered by the MMHUs in rural Greece may reduce the number of hospitalizations, both voluntary and involuntary, as well as the length of hospital stay in patients with severe mental illness [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of hospitalizations did not differ statistically between the two groups of patients. It has been previously shown that treatment delivered by the MMHUs in rural Greece may reduce the number of hospitalizations, both voluntary and involuntary, as well as the length of hospital stay in patients with severe mental illness [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the estimation of the impact of the delivered care on patients' outcomes we applied a mirror image, prepost comparison of patients' outcome measures, i.e., hospitalizations, psychopathology and functioning, for the same interval prior and after engagement with the hybrid ACT care. This methodology has been previously used in research in community mental healthcare settings [24,31,32].…”
Section: Study Proceduresmentioning
confidence: 99%
“…The MMHUs are integrated within the primary healthcare system and examine all referrals, with a special focus on patients with SMI [30]. There is preliminary evidence that the MMHUs may be effective in the treatment of both severe and common mental disorders and may reduce hospitalizations and disease-related disability [31][32][33]. Although previous research on SMI patients has shown that attendance rate with the MMHUs is satisfactory [34], still a substantial proportion, that is almost one-third disengage from care.…”
Section: Introductionmentioning
confidence: 99%
“…In general, research in the context of MMHUs is scarce and has been mostly conducted on islands [10][11][12] and on one site on the mainland [13][14][15][16]. Notably, most studies are single-center, which may limit the generalizability of their findings [17].…”
Section: Fragmentation In Researchmentioning
confidence: 99%